EFEKTIVITAS JOINT PRESS STATEMENT DALAM MENANGGULANGI ANCAMAN ABU SAYYAF DI WILAYAH PERBATASAN INDONESIA-FILIPINA - M. Herry Misya; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is a security study that provides an analysis of the problem of overcoming the problem of hostage taking by the Abu Sayyaf Group at the Indonesia-Philippines border through the Joint Press Statement Forum as a forum of cooperation between Indonesia and the Philippines.This research uses a conceptual foundation, applying the national interest concept of program implementation to see how much of its influence in the effort to save the Indonesian citizen hostage by the Abu Sayyaf Group on the Indonesia-Philippines border by focusing on a particular region. Supported by the theory of international cooperation. The concept leads to qualitative methods and literature study as a source of information.Some of Indonesia’s effort in overcoming the core problem is to monitor the forum until all citizens are free from hostage by Abu Sayyaf. So far these efforts have provided poor results to government of Indonesia because the Philippines has not given direct rights to Indonesia to directly diplomate with the Abu Sayyaf.Keywords: Abu Sayyaf, Terorism, International Cooperation, Indonesia-Philippines